Mechanisms and moderators of behavioural couples therapy for alcohol and substance use disorders: an updated review of the literature. Issue 3 (22nd May 2022) - Mutschler, Christina; Malivoire, Bailee L.; Schumm, Jeremiah A.; Monson, Candice M.
Abstract: Introduction: Behavioural couples therapy (BCT) and alcohol behavioural couples therapy (ABCT) are couples-based interventions for substance use disorders (SUDs) that have been deemed a 'gold standard' treatment. Despite the substantial amount of promising research, there is a lack of research on the active components of treatment and treatment mechanisms and moderators. Since the most recent meta-analysis, a number of studies have been conducted that advance our understanding of the efficacy of BCT and ABCT. Aims: The purpose of the present review was to provide an update on the current knowledge of these treatments and to investigate mediators and moderators of treatment. Method: A systematic search strategy of relevant databases from 2008 to 2021 identified 20 relevant articles that were coded for relevant information including study design, treatment, outcomes, as well as mechanisms and moderators. Results: The results indicated that BCT and ABCT are successful in reducing alcohol and substance use for both male and female clients, dual problem couples, and for reducing post-traumatic stress symptoms and intimate partner violence. The reviewed studies discussed a number of treatment mechanisms, with the most studied mechanism being relationship functioning. Moderators included relationship functioning and patient gender. Conclusions: The results point to the need for additional research on active treatment components, mechanisms and moderators, in order to provide a more efficient and cost-effective treatment.